2000
DOI: 10.1037/0021-843x.109.3.396
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive abilities in adolescent-limited and life-course-persistent criminal offenders.

Abstract: T. E. Moffitt's (1993a) hypothesis that adolescent-limited criminal offenders will have higher scores on tests of cognitive ability than life-course-persistent offenders was tested with 12 tests of cognitive ability given to a large and diverse sample of delinquent juveniles whose arrest records were collected over 20 years. This is the first investigation to empirically evaluate this proposal with longitudinal data obtained from a sample for a long enough time to distinguish life course patterns of crime. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 23 publications
0
50
1
Order By: Relevance
“…These results indicate that not only are Indigenous Australians more likely to offend, but when they do offend, they exhibit more chronic and serious offending patterns. This mirrors what we know about the relation between race/ethnicity and offending over the life course in US samples, particularly those focusing on differences between African Americans and Whites [32,82,101].…”
Section: Indigenous Status and Life Course Offending Patternsmentioning
confidence: 81%
See 1 more Smart Citation
“…These results indicate that not only are Indigenous Australians more likely to offend, but when they do offend, they exhibit more chronic and serious offending patterns. This mirrors what we know about the relation between race/ethnicity and offending over the life course in US samples, particularly those focusing on differences between African Americans and Whites [32,82,101].…”
Section: Indigenous Status and Life Course Offending Patternsmentioning
confidence: 81%
“…The few life course studies to examine race/ethnicity focus primarily on the experiences of Blacks, although some recent work outlines longitudinal offending patterns among samples of Hispanics [51,63]. Studies comparing Blacks to Whites indicate that Blacks populate chronic offending trajectories at significantly higher rates than Whites [32,64,82,101] and that this reflects their unique structural contexts and related exposure to key risk factors that both foster early onset and preclude desistance [48,84].…”
Section: Race/ethnicity and Life Course Offending Trajectoriesmentioning
confidence: 99%
“…232 Brain science demonstrates that complete social and emotional maturity does not occur until age twenty-five. 233 Most criminal offenders have not reached that age. 234 It is difficult, then, to measure one's future dangerousness given the uncertainty of physical and emotional development.…”
Section: The Evolving Standards Of Decencymentioning
confidence: 99%
“…(2000). Data from the California Youth Authority (CYA), found that cognitive abilities identified differences between adolescence-limited and life-course-persistent offenders, but no relationship was found between cognitive abilities and crime types among African-Americans (Donnellan et al 2000). Using the same data Ge, Donnellan, and Wenk (2001) examined patterns of chronic offenders within the CYA offenders.…”
Section: Moffitt's Dual Taxonomymentioning
confidence: 99%
“…To date, when studies have examined the role of race, they have used it as a control measure and not as a central feature of the study. For instance, two studies show that this is an issue (Donnellan, Ge, & Wenk, 2000;Piquero, Moffitt, & Lawton, 2005). Piquero, Moffitt, and Lawton (2005) provide two cogent rationales why this is the case.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%